HEALTHY LIFESTYLE - Shermatova Yokutkhon, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
a healthy lifestyle in this article consists of the fact that a person, following his daily routine, constantly tempers his body on the basis of active action, regularly goes in for sports, eats quality in full compliance with hygienic rules, is able to keep his own from harmful vices, to keep meaningful until the end of a given life.